Studies in Mexican Grasshoppers: A new species of Pedies Saussure (Acrididae: Melanoplinae) with comments on the unusual blue coloration on the abdomens of females and live specimen images for three other congenerics - Mariño-Pérez, Ricardo; Fontana, Paolo; Woller, Derek A. (Zootaxa, 2018)
A new species of Melanoplinae (Orthoptera: Acrididae) is described from Central Mexico: Pedies andreae sp. nov. Fontana, Mariño-Pérez, & Woller and is added to the 12 existing species. Taxonomic placement of this species is justified based on distinct morphology and comparisons with congeneric species are provided. Additionally, species in this genus are associated with higher elevations (1,700 to 3,700 masl) that possess larger fluctuations in temperatures. We observed that females of P. andreae sp. nov. exhibit blue coloration on their abdomens and we discuss the possible reasons for this peculiar pigmentation. Interestingly, we did not observe this coloration in males. Finally, images are provided for three live previously described species of Pedies.